Hubungan Bahasa dan Pikiran dalam Perspektif Sintaksis dan Pragmatik - Fika Rahmayani; Julita Dwi Anggraeni; Rosda Aisyatul A’izzi; M. Yunus Abu Bakar (JURNAL ILMIAH NUSANTARA, 2026)
This study examines the relationship between language and thinking from the perspectives of syntax and pragmatics. Language is not only used for communication but also reflects how humans organize thoughts and concepts. From a syntactic perspective, patterns and rules in grammar show how humans organize ideas in an orderly manner. From a pragmatic perspective, language use depends on the social situation, the purpose of speaking, and the understanding of meaning, which indicates how the thought process occurs in interactions. This study uses a qualitative approach by seeking information from various books and articles discussing linguistics and the philosophy of language. The results show that the relationship between language and thought is mutually influential: thoughts shape the way language is structured, while language influences how humans think and understand the world. In conclusion, syntax and pragmatics are two important, complementary parts in explaining the relationship between language structure and human thought processes.